The relative contributions of reabsorptive rate and redistributed nephron filtration rate to changes in proximal tubular fractional reabsorption during acute saline infusion and aortic constriction in the rat - Bartoli, Ettore (J Clin Invest, 1971)
The absolute rate of reabsorption by superficial rat proximal tubules was measured by the in situ microperfusion technique under conditions of hydropenia, infusion of saline, and infusion of saline plus aortic constriction sufficient to decrease whole kidney filtration rate below hydropenic levels. Fractional reabsorption was measured in adjacent filtering nephrons by collecting and recollecting tubular fluid from late proximal convolutions during each experimental condition. During hydropenia, the absolute rate of proximal tubular reabsorption averaged 3.56 ±0.60 nl/min per mm and late proximal tubular fractional reabsorption averaged 0.56 ±0.10. From these two measurements and measurements of tubule length to the site of micropuncture, a value for filtration rate was calculated for filtering nephrons. During hydropenia this value averaged 32.9 ±7.1 nl/min. Saline infusion increased sodium excretion to 5.5% of the filtered load as the absolute rate of proximal tubular reabsorption decreased 38% and fractional reabsorption decreased 45%. Calculated superficial nephron filtration rate increased 21% which on the average was identical with the simultaneously measured increase in whole kidney filtration rate. Similar results were obtained in a separate group of animals by the technique of total collection of late proximal tubular fluid. Aortic constriction during saline infusion decreased whole kidney and calculated nephron filtration rate to the same degree and to values lower than those during hydropenia. Fractional reabsorption increased but not to hydropenic values. The persistent natriuresis during aortic constriction was associated with a continued depression of the absolute rate of proximal tubular reabsorption which was sufficient to maintain an increased delivery of filtrate out of the proximal tubule despite the fall in nephron filtration rate. These results indicate that depressed fractional reabsorption in the proximal tubule during acute saline infusion is due predominantly to a decrease in absolute reabsorptive rate and to a lesser extent to an increase in superficial nephron filtration rate which is proportional to the increase in whole kidney filtration. Continued natriuresis when filtration rate is decreased during saline infusion can be accounted for entirely by the persistent large reduction in the absolute rate of proximal tubular reabsorption.